2021
DOI: 10.1101/2021.03.30.21254644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in opioid and psychostimulant craving and relapse: a critical review

Abstract: A widely held dogma in the preclinical addiction field is that females are more vulnerable than males to drug craving and relapse. Here, we first review clinical studies on sex differences in psychostimulant and opioid craving and relapse. Next, we review preclinical studies on sex differences in psychostimulant and opioid reinstatement of drug seeking after extinction of drug self-administration and incubation of drug craving (time-dependent increase in drug seeking during abstinence). We also discuss ovarian… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 216 publications
(200 reference statements)
2
11
0
Order By: Relevance
“…Another finding in our study was that, in the vehicle condition, we found no evidence for sex differences in the four relapse‐related measures. These results agree with those from our previous study with oxycodone in which we did not observe sex differences in extinction responding, context‐induced reinstatement and reacquisition (Bossert et al, 2020), and other studies using the extinction‐reinstatement procedure showed similar magnitude of reinstatement of opioid seeking in males and female rats (Nicolas et al, 2021). Our negative sex differences data also agree with those from our recent studies on relapse to opioid seeking after voluntary abstinence induced by either providing rats with alternative rewards (palatable food or social interaction) in a choice procedure or exposing them to an electric barrier near the drug‐paired lever (Fredriksson et al, 2020, 2021; Reiner et al, 2020; Venniro et al, 2017, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Another finding in our study was that, in the vehicle condition, we found no evidence for sex differences in the four relapse‐related measures. These results agree with those from our previous study with oxycodone in which we did not observe sex differences in extinction responding, context‐induced reinstatement and reacquisition (Bossert et al, 2020), and other studies using the extinction‐reinstatement procedure showed similar magnitude of reinstatement of opioid seeking in males and female rats (Nicolas et al, 2021). Our negative sex differences data also agree with those from our recent studies on relapse to opioid seeking after voluntary abstinence induced by either providing rats with alternative rewards (palatable food or social interaction) in a choice procedure or exposing them to an electric barrier near the drug‐paired lever (Fredriksson et al, 2020, 2021; Reiner et al, 2020; Venniro et al, 2017, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Preclinical studies reveal that there are relatively fewer sex differences associated with opioid-related behaviors, including relapse ( Nicolas et al, 2021 ). Here, males and females show similar patterns of relapse-like behavior, and yet females do not display an increase in 50-kHz USVs during the late abstinence relapse test when craving is high.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to men, women are likely to consume more cocaine, can have a shorter latency from first cocaine use to abuse, and can be more vulnerable to craving and relapse after abstinence (Elman et al, 2001;Haas & Peters, 2000;McCance-Katz et al, 1999;McKay et al, 1996) but see (Nicolas et al, 2021). Similar sex differences are also reported in rats (Algallal et al, 2020;Becker & Koob, 2016;Calipari et al, 2017;Lynch & Carroll, 2000;Lynch, 2017;Nicolas et al, 2021;Roberts et al, 1989;Roth & Carroll, 2004). Some, but not all, of these sex differences involve estradiol.…”
Section: Introductionmentioning
confidence: 79%
“…Cocaine addiction afflicts both women and men, and studying addiction treatments in both female and male subjects is especially important because the sexes can differ in the transition to addiction (Becker, 2017;Becker & Koob, 2016;Carroll & Lynch, 2016). Compared to men, women are likely to consume more cocaine, can have a shorter latency from first cocaine use to abuse, and can be more vulnerable to craving and relapse after abstinence (Elman et al, 2001;Haas & Peters, 2000;McCance-Katz et al, 1999;McKay et al, 1996) but see (Nicolas et al, 2021). Similar sex differences are also reported in rats (Algallal et al, 2020;Becker & Koob, 2016;Calipari et al, 2017;Lynch & Carroll, 2000;Lynch, 2017;Nicolas et al, 2021;Roberts et al, 1989;Roth & Carroll, 2004).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation